2020
DOI: 10.1111/ijpo.12734
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota in adolescent girls with polycystic ovary syndrome: Effects of randomized treatments

Abstract: Summary Background Girls with obesity and polycystic ovary syndrome (PCOS) and women with PCOS have altered gut microbiota. Objective To study the gut microbiota composition of girls with PCOS without obesity (age, 15.8 years; body mass index [BMI] 25 kg/m2) and the effects of randomized treatments with an oral contraceptive (OC, N = 15) or with spironolactone‐pioglitazone‐metformin (SPIOMET, N = 15) for 1 year. Thirty‐one age‐matched girls served as controls. Methods 16S ribosomal subunit gene amplicon sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…A recent study contrasted changes in the gut microbiome in Catalonian adolescents with PCOS without obesity before and after treatment with OCP and combination of spironolactone, pioglitazone, and metformin (SPIOMET). ( Garcia-Beltran et al, 2021 ) No differences in α- or β-diversity were noted after treatment in the OCP group, the group receiving SPIOMET exhibited a reduction in the relative abundance of Family XI alongside reductions in hepato-visceral fat. It is possible that changes in the gut microbiome and downstream effects on host physiology may have occurred following SPIOMET, but not OCP use, because of direct actions on the microbiome.…”
Section: Discussionmentioning
confidence: 91%
“…A recent study contrasted changes in the gut microbiome in Catalonian adolescents with PCOS without obesity before and after treatment with OCP and combination of spironolactone, pioglitazone, and metformin (SPIOMET). ( Garcia-Beltran et al, 2021 ) No differences in α- or β-diversity were noted after treatment in the OCP group, the group receiving SPIOMET exhibited a reduction in the relative abundance of Family XI alongside reductions in hepato-visceral fat. It is possible that changes in the gut microbiome and downstream effects on host physiology may have occurred following SPIOMET, but not OCP use, because of direct actions on the microbiome.…”
Section: Discussionmentioning
confidence: 91%
“…has been shown to decrease just after the metformin treatment. The relative abundance of Senegalimassilia spp has also been reported to be reduced in human polycystic ovarian syndrome cases 46 , and overweight children compared to the normal weight ones 47 . In conclusion, it can be said that TA, which is currently used in the treatment of type 2 diabetes, may have the potential to reverse the side effects of the widely used medication metformin.…”
Section: Discussionmentioning
confidence: 97%
“…has been shown to decrease just after the metformin treatment. The relative abundance of Senegalimassilia spp has also been reported to be reduced in human polycystic ovarian syndrome cases 46 , and overweight children compared to the normal weight ones 47 .…”
Section: Discussionmentioning
confidence: 97%
“…We identified 14 human studies that compared the microbiota of patients diagnosed with PCOS with a variety of control groups [29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Ten of the 14 studies reported reduced alpha diversity in the PCOS group compared to the control populations [29][30][31][35][36][37][38][39][40]42].…”
Section: Dysbiosismentioning
confidence: 99%